Identification of Novel Modifiers of Tau Aggregation and Pathology using a Proximity Proteomics Approach. (20th December 2022) - Lee, Jannifer H; Morderer, Dmytro; Khalil, Bilal; Liu, Feilin; Tsai, Chih‐Wei; Croft, Cara L; Carlomagno, Yari; DeTure, Michael; Salemi, Michelle; Cook, Casey; Phinney, Brett; Dickson, Dennis W.; et al.
Abstract: Background: Alzheimer's disease (AD) and related neurodegenerative diseases are characterized by the accumulation of abnormal protein aggregates. A defining hallmark of AD is the formation of neurofibrillary tangles (NFTs) by aggregation of the microtubule‐associated protein tau into pathological oligomers and fibrils. Although NFTs are believed to play a pivotal role in the disease process, we have a poor understanding of how their formation, toxicity, and spread across brain regions is regulated. Recent data suggest that the seeding behavior of tau is governed by patterns of posttranslational modifications and varying filament structures. Understanding how tau‐associated proteins regulate the oligomerization, pathological accumulation, and seeding of tau in affected neurons and glia is of critical importance for therapy development. Method: To profile the interactome of tau aggregates, we have established proximity‐dependent biotin‐identification (BioID) as a novel method to identify the composition and proximal molecular environment of insoluble protein aggregates in the context of living brain cells and tissue. Using an in vitro and ex vivo model approach coupled with mass spectrometry, we are generating datasets containing top identified proteins, stratified based on significance and molecular pathway. Once we validate their co‐localization with NFTs in the context of human AD pathology, functional characterization of putative modifiers will be performed to assess their impact on tau‐aggregate and toxicity. Result: To determine the physiological and aggregate specific interacting partners of tau, we are comparing wild type tau (TauWT) with mutant tau (Tau3xMUT) carrying three tauopathy‐associated mutations (A152T/P301L/S320F) that form hyper‐phosphorylated and thioflavin S‐positive aggregates even in the absence of seeding. The proteomic analysis from our pilot study revealed that significantly changed proteins included candidates involved in RNA processing, as well as protein ubiquitination and proteasome degradation. Conclusion: This study provides novel insights into cellular pathways and molecular mechanisms of neurodegeneration, by identifying in the context of living neurons and brain tissue different functional classes of tau‐associated proteins with relevance for AD pathophysiology. These are expected to include proteins that may mediate the toxic effect of NFTs, facilitate the formation or degradation of pathological tau aggregates, and catalyze posttranslational modifications of tau oligomers and associated proteins.